“CARTÕES POSITIVOS”: MENTAL HEALTH PROMOTION EXPERIENCE REPORT - de Souza Cintra, Joanna Darc; Cavalcanti de Freitas, Ana Carina; da Fonseca de Santacruz, Lusanira Maria (Cadernos ESP, 2023)
This article aims to report the experience of mental health care of health workers who work in a Health District of the municipality of Recife, Pernambuco. The action called “Positive Cards” was developed based on the memory card technique (flash cards). It consisted of offering small cards with affirmative phrases and positivity, fixed at two points in the building. Data were analyzed quantitatively and presented descriptively. We also used comments, praise and criticism made by service workers during the implementation of the action as an evaluation. In 30 days, 300 cards were distributed. High demand, low cost and easy reproducibility were some of the positive points observed; low control of participants, fragile material and constant maintenance were negative points observed. This action is an easily reproducible intervention idea, with clear language, which presents minimal risk to participants and can generate a positive effect on participants.
Keywords: Employee Health; Mental Health; Public Health